Cardiorespiratory and Autonomic Nervous System Responses to Prolonged Eccentric Cycling - Ritter, Ophélie; Isacco, Laurie; Rakobowchuk, Mark; Tordi, Nicolas; Laroche, Davy; Bouhaddi, Malika; Degano, Bruno; Mourot, Laurent (International Journal of Sports Medicine, 2019)
Offering large muscle benefits despite low metabolic demand, continuous eccentric exercise appears to be an interesting alternative to concentric exercise. Nevertheless, further knowledge is needed about prolonged eccentric exercise. This work sought to investigate the cardiovascular responses to prolonged constant-load eccentric compared to concentric cycling. Ten healthy males performed two 45-min exercise sessions of either concentric or eccentric cycling separated by a month and matched for heart rate during the first 5 min of exercise. Cardiorespiratory, autonomic nervous system and vascular responses were assessed at rest, and during exercise and recovery. During cycling, oxygen uptake, cardiac output and systolic blood pressure were similar but heart rate and diastolic blood pressure were greater whereas stroke volume was lower during eccentric than concentric cycling (118±21 vs. 104±10 bpm; 77±9 vs. 65±8 mmHg; 122±12 vs. 135±13 mL). Baroreflex and noradrenaline concentration were altered during eccentric cycling, and after eccentric exercise, vascular tone was greater than after concentric cycling. We observed increased cardiovascular strain and altered baroreflex activity during eccentric compared with concentric exercise, suggesting eccentric cycling triggers greater sympathetic activity.
Keywords: cardiovascular strain; baroreflex activity; respiratory responses; continuous endurance exercise